Root morphology and distribution of paddy rice and their relationship with nutrient uptake and grain yield - Abichequer, André Dabdab (2008)
The development of more efficient genotypes in nutrient uptake is one of the factors that can result in yield increases in paddy rice (Oriza sativa L.), besides lowering fertilizer need, by reducing nutrient losses and improving nutrient use. Nutrient uptake efficiency can be related to root morphology and distribution in soil. A field experiment was conducted in a Gleissolo, in Cachoeirinha (RS – Brazil), to compare genotypes of different plant types: IRGA 417 (modern), EEA 406 (traditional), Avaxi (hybrid, modern) and Bluebelle (american) in relation to root density, root surface area and root radio, nutrient uptake (P and K) and grain yield. Root distribution (depth 0 to 5, 5 to 20, 20 to 30 and 30 to 40 cm) was sampled by monolith method. Genotypes differed in root morphology and distribution, with ‘Avaxi’ and ‘EEA 406’ having higher root density and a more superficial distribution, especially ‘Avaxi’. Modern genotypes (IRGA 417 and Avaxi) had greater grain yield. Genotypes differed in nutrient uptake only by K uptake on mature grain stage, when ‘IRGA 417’ and ‘Avaxi’ had greater uptake than ‘EEA 406’. There was no relationship between root morphology and distribution in soil with nutrient uptake and grain yield.